Understanding Dynamic Capabilities from Its Antecedents, Processes and Outcomes - Tondolo, Vilmar Antônio Gonçalves (2014)
The theory of Dynamic Capabilities has been one of the references in the search for understanding of the competitive advantage of organizations. However, even with the development of studies on this topic, it is not clear how the Dynamic Capabilities develop and operate within organizations. Thus, this study aims to understand the dynamics capabilities from its antecedents, processes and outcomes. Through a literature review, it was possible to identify external and internal antecedents that make Dynamics Capabilities emerge in organizations, such as environmental dynamism and corporate entrepreneurship. In when it comes to process, it was identified that the Dynamic Capabilities are formed by a set of processes that have effect on resources and organizational capabilities. Thus, the development of resources and capabilities is the outcome of Dynamic Capabilities. Finally, unlike other studies, this work considers the DCs not as a specific capacity, but as a set of processes that enable the organization to deal with changes in the competitive environment.